1994
DOI: 10.2172/10149785
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation survey of knapweed on the Yakima Training Center - 1992

Abstract: This report summarizes and discusses the results of a vegetation survey conducted in 1992 on a portion of the YakimaTrainingCenter (YI"C). PacificNorthwestLaboratory(PNL) conductedthis surveyand a similarsurveyin 1991 for the U.S. Departmentof the Army. The objectivesof the surveywereto evaluatethe impactof the herbicidepicloramon forbs where aerial applicationsof picloramweremade in 1988, 1989, and i991 to controlknapweed (Centaureaspp.) infestations.Forbsare of specialinterestbecausethey are an importantpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Hoping to gain additional insight into the reasons that sage grouse may prefer or avoid spray areas, we examined data collected by Downs et al (1994) relative to forb cover in several spray areas. They found that the 1991 spray area had less knapwced and fewer perennial forbs than the control area in 1991.…”
Section: Use Of Knapweed Spray Areasmentioning
confidence: 99%
“…Hoping to gain additional insight into the reasons that sage grouse may prefer or avoid spray areas, we examined data collected by Downs et al (1994) relative to forb cover in several spray areas. They found that the 1991 spray area had less knapwced and fewer perennial forbs than the control area in 1991.…”
Section: Use Of Knapweed Spray Areasmentioning
confidence: 99%